AI-Assisted Searching Through Crowdsourced Solution Space - Julian Wahl; Johann Füller; Katja Hutter (Marketing Review St.Gallen, 2022)
In crowdsourcing contests, managers have to process hundreds of potential solutions on different topics and from different perspectives. This is resource-intensive, and the cognitive limits of humans are quickly exceeded. Applying contemporary AI-based language models is a promising way to help structure and explore crowdsourcing solutions.
Keywords: 650